AUSONIO EN EL EPIGRAMA LATINO HUMANISTA Y SU INFLUENCIA EN EL MURCIANO FRANCISCO CASCALES - Ramos Maldonado, Sandra (Myrtia, 1996)
Presence of Ausonius in F. Cascales’ epigrams, who evokes him through certain more or less lucky games, withort falling in anything neoteric in excess, as it should be expected from a poet who defines himsey as a epigrammatizer and a strong oppositer, in the «war» which took place between the «fair» and teh «dark» in the early XVII century, of the vice of darkness, the new inventions and the extravagant workmanship.